An Evaluation of Sindh Schools Education System: Problems and Possibilities - Khoso, Zamir Ahmed; Siddiqui, Mazhar Ali; Tagar, Ali Akbar; Tagar, Hamzo Khan (Advances in Social Sciences Research Journal, 2019)
This paper has been written in the context of quality education in Sindh province of Pakistan. The system has been examined through descriptive manner and in a broad context to sort out the major problems of the system, and also to provide feasible policy recommendations to improve the system in the greater public interest. Because literacy is a weapon of the 21st century to fight with poverty, illiteracy, hunger, socio-economic evils and with global terrorism to secure and safeguard the rights of future generations. Through this paper, the Government of Sindh has been updated about grey areas in their education system, feasible solutions which includes, merit and need-based recruitment of teachers, pre-service teachers trainings, condition of teachers license, posting of competent teacher as “ head teacher”, appointment of professional officers against managerial positions, curriculum and textbook development, re-opening of feasible closed schools through intervention of public-private partnership node and Sindh Education Foundation, development of education policy based on Standardized Achievement Test ( SAT) and Provincial Education Assessment Center (PEACE) results / reports and establishment of one model primary (Male & Female) and Secondary School in each tehsil of the district with all required facilities, including adequate budget to create competitive atmosphere amongst public and private sector schools. The implementation of formal and non-formal education and re-vitalization of vocational and technical institutions have also been recommended to create employment for youths.